Development of a learning leadership model for vocational high school principals to foster student well-being within the framework of Merdeka Belajar - Yuliana, Lia; Prasojo, Lantip Diat; Akalili, Awanis; Firdaus, Fery Muhamad (LPMPP Universitas Negeri Yogyakarta, 2025)
This study aims to (1) determine the necessity of a learning leadership model for vocational school principals to realise student well-being in the context of Merdeka Belajar, (2) develop a theoretically and empirically valid learning leadership model for vocational high school principals to achieve student well-being (KPK-SW model) within the context of Merdeka Belajar, and (3) assess the effectiveness of the learning leadership model for vocational high school principals in achieving student well-being within the Merdeka Belajar framework. This research employed the Research and Development method, consisting of four phases: the initial phase, the planning phase, the testing, evaluation, and revision phase, and the implementation phase. The testing process was carried out in three stages: an initial trial involving 10 experts and education practitioners. The data were collected through focus group discussions, questionnaires, documents, observations, and interviews. The validity and reliability of the questionnaire instruments were ensured through expert validation. The validity of qualitative data was confirmed through informant review and data triangulation models. Quantitative data analysis was done using descriptive analysis techniques, while qualitative data was analysed using an interactive analysis model. The research findings indicate that the KPK-SW model fosters student well-being. The level of importance, according to users, includes scores of 4.44 from the Head of the Education Department of DIY, 4.39 from school supervisors, 3.32 from the Secondary Education Office, and 4.38 from education experts. The total average score is 4.38, suggesting this model is highly significant and suitable for implementation.